Kepemimpinan yang Kuat Dalam Manajemen Pendidikan Islam Perspektif Hadis - Dadan F. Ramdhan (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2023)
This study aims to reveal strong leadership in the management of Islamic education perfective hadith. This research uses qualitative research methods with a descriptive approach to literature studies. The results and discussion of this research show that the figure of a strong leader in an education management has a meaning, they are the ones who are able to be responsible, trustworthy and professional at work. This research concludes that strong leadership is a recommendation in Islamic teachings, even in the hadith it is said that a strong believer is better and more Allah loves than a weak believer, this study recommends that a leader should have and master the principles of carrying out management in an education. Keywords: Management; Leader; Hadith